Investigation of fundamental properties of nanorefrigerants / Mohammed Mahbubul Islam - Mohammed Mahbubul Islam, - (2012)
In the past decade, rapid advancements of nanofluids science in many areas have been observed. In recent years, refrigerant-based nanofluids have been introduced as nanorefrigerants due to their better heat transfer performance. The objectives of this research include preparation, characterization and investigation of the thermophysical and migration properties of nanorefrigerants. Al2O3/R141b and TiO2/R141b nanorefrigerants with various proportions of concentrations have been prepared to investigate their fundamental properties. Nanoparticles size, shape, and elemental proportion have been characterized with Field Emission Scanning Electron Microscope (FESEM) and Transmission Electron Microscope (TEM). Moreover, this study investigated thermal conductivity, viscosity, and density of Al2O3/R141b nanorefrigerants for different concentrations and temperatures. In addition, migration properties of Al2O3 and TiO2 nanoparticles with R141b refrigerant along with lubricating oil have been investigated for different heat fluxes, initial liquid level heights, vessel sizes, insulation, nanoparticle sizes, and oil mixture. In this study, the thermal conductivity of Al2O3/R141b nanorefrigerant increased with the augmentation of particle concentration and temperature. Besides, viscosity and density of the nanorefrigerant increased with the increase of volume fractions. However, these parameters decreased accordingly with the increment of temperature. Migration of nanoparticles during pool boiling increased with the increase of initial nanoparticle mass fraction, nanoparticle size, heat flux, and insulation. However, migration of nanoparticles decreased with the increase of particle’s self-density, boiling vessel size, and initial liquid level height. Therefore, nanoparticle has strong relationship with thermophysical and migration properties of refrigerants.